Collision tumor of thyroid gland a case report - kadam, satar majeed; Ibraheem, Nadia H.; Al-Rubaei, Nabeel J. (Journal of the Faculty of Medicine Baghdad, 2020)
collision tumor is the presence of two histopathologically distinct tumors in the same anatomical site. It is a rare pathology of the thyroid gland that makes diagnosis and treatment challenging. This is a case report of a collision tumor of the thyroid gland.